Risk Factor Analysis for Stroke Incidence in North Sulawesi: Based on the 2018 Indonesia Basic Health Research - Lia Mulyani; Avliya Quratul Marjan; Firlia Ayu Arini; Yessi Crosita Octaria (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Stroke is a serious public health issue and the main cause of disability and death after ischemic heart disease. Every year, 12.2 million individuals worldwide suffer from a stroke, which results in 6.5 million deaths. There has been an increasing incidence of stroke in Indonesia, including in North Sulawesi. This study aims to examine the risk factors for stroke incidence in North Sulawesi in a population aged ≥35 years based on the 2018 Indonesia Basic Health Research data. This quantitative research was an analytical observational study with a cross-sectional design. The Chi-square test and multiple logistic regression were performed during data analysis involving 7,111 respondents. The multivariate analysis results showed that hypertension (p=0.000; AOR 8.739; 95% CI 5.758-13.263), physical activity (p=0.000; AOR 2.771; 95% CI 1.944-3.948), gender (p=0.000; AOR 2.047; 95% CI 1.388-3.017), heart disease (p=0.015; AOR 1.919; 95% CI 1.133-3.250), age (p=0.008; AOR 1.669; 95% CI 1.144-2.434), occupation (p=0.008; AOR 1.693; 95% CI 1.145-2.504), and fatty foods consumption (p=0.023; AOR 0.603; 95% CI 0.390-0.932) had a significant correlation with stroke incidence in this study. The main finding of this study shows that hypertension is the most influential risk factor for stroke incidence in a population aged ≥35 years in North Sulawesi. Regular blood pressure screenings are needed as an early hypertension detection effort to prevent stroke incidence.